2001
DOI: 10.1051/0004-6361:20000144
|View full text |Cite
|
Sign up to set email alerts
|

ISO spectroscopy of circumstellar dust in 14 Herbig Ae/Be systems: Towards an understanding of dust processing

Abstract: Abstract. We present Infrared Space Observatory (ISO) spectra of fourteen isolated Herbig Ae/Be (HAEBE) stars, to study the characteristics of their circumstellar dust. These spectra show large star-to-star differences, in the emission features of both carbon-rich and oxygen-rich dust grains. The IR spectra were combined with photometric data ranging from the UV through the optical into the sub-mm region. We defined two key groups, based upon the spectral shape of the infrared region. The derived results can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

74
806
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(887 citation statements)
references
References 29 publications
(52 reference statements)
74
806
1
1
Order By: Relevance
“…This result is in line with previous near-IR and optical measurements that suggest that Herbig Be stars have geometrically flatter disks than Herbig Ae and T Tauri stars (see e.g. Meeus et al 2001) The flattening of the disk in Herbig Be stars can be due to the rapid grain growth. The grain growth causes the optical depth of the disk to drop and allows the UV radiation to penetrate deep into the circumstellar disk and photo-evaporate the disk external layers (Dullemond & Dominik 2004).…”
Section: R Monsupporting
confidence: 92%
“…This result is in line with previous near-IR and optical measurements that suggest that Herbig Be stars have geometrically flatter disks than Herbig Ae and T Tauri stars (see e.g. Meeus et al 2001) The flattening of the disk in Herbig Be stars can be due to the rapid grain growth. The grain growth causes the optical depth of the disk to drop and allows the UV radiation to penetrate deep into the circumstellar disk and photo-evaporate the disk external layers (Dullemond & Dominik 2004).…”
Section: R Monsupporting
confidence: 92%
“…It was shown that the more red objects were displaying more extended emission than that of the more blue sources. Such a result is consistent with the classification of Meeus et al (2001) where the group I flared disks are redder and which mid-IR emission appears larger, whereas the group II flat self-shadowed disks present a more compact mid-IR emission.…”
Section: Inner Disk Regions: Observational Findingssupporting
confidence: 90%
“…Because our current knowledge is biased towards flared disks which are much easier to detect since they intercept more starlight, it is possible that undetected disks represent a more advanced, settled state in disk evolution. In the specific case of intermediate-mass Herbig Ae stars, SED analyses have led to a picture in which, for so-called "group II" (Meeus et al, 2001), the outer disk lies in the shadow cast by the inner regions, reducing the chances to detect the disk in scattered light. Indeed, only two of the 10 disks imaged in scattered light around Herbig stars pertain to the group II discussed above.…”
Section: Inner Disk Regions: Observational Findingsmentioning
confidence: 99%
“…Mid-infrared spectroscopic observations are sensitive to dust properties including size distribution and composition which in turn probe the physical conditions in the disk [7]. We will determine, for example, the relative importance of broad features attributed to amorphous silicates (ubiquitous in the ISM) compared to numerous narrow features throughout the 5.3-40 µm region due to crystalline dust (observed only in circumstellar environments [12]). In this way, we can diagnose radial mixing in the disk because the temperature required to anneal grains (> 1500K) is substantial higher than the inferred temperature of the emitting material (∼ 300K).…”
Section: Formation Of Planetary Embryosmentioning
confidence: 99%